Infections and nutrient deficiencies during infancy predict impaired growth at 5 years: Findings from the MAL-ED study in Pakistan - González-Fernández, Doris; Cousens, Simon; Rizvi, Arjumand; Chauhadry, Imran; Soofi, Sajid Bashir; Bhutta, Zulfiqar Ahmed (Frontiers in Nutrition, 2023)
Socio-economic, nutritional, and infectious factors have been associated with impaired infant growth, but how the presence of these factors during infancy affects growth around 5 years is not well understood. Methods: This secondary analysis of the MAL-ED cohort included 277 children from Pakistan for whom socio-demographic, breastfeeding, complementary foods, illness, nutritional biomarkers, stool pathogens and environmental enteropathy indicators between 0-11 months were recorded. We used linear regression models to analyze associations of these indicators with height-for-age (HAZ), weight-for-age (WAZ) and weight-for-height (WLZ) at 54-66 months ( 5y), and Poisson regression with robust standard errors to estimate risk ratios for stunting and underweight 5y, controlling for gender, first available weight, and income. Results: Among the 237 infants followed longitudinally and evaluated at about 5 years of age, exclusive breastfeeding was short (median= 14 days). Complementary feeding started before 6 months with rice, bread, noodles, or sugary foods. Roots, dairy products, fruits/vegetables, and animal-source foods were provided later than recommended (9-12 months). Anemia (70.9%), deficiencies in iron (22.0%), zinc (80.0%), vitamin A (53.4%) and iodine (13.3%) were common. Most infants (>90%) presented with diarrhea and respiratory infections in their first year. At 5y, low WAZ (mean -1.91 ± 0.06) and LAZ (-2.11 ± 0.06) resulted in high prevalence of stunting (55.5%) and underweight (44.4%) but a relatively low rate of wasting (5.5%). While 3.4% had concurrent stunting and wasting 5y, 37.8% of children had coexisting stunting and underweight. A higher income and receiving formula or dairy products during infancy were associated with a higher LAZ 5y, but infant’s history of hospitalizations and more respiratory infections were associated with lower LAZ and higher risk of stunting 5y. Infants’ intake of commercial baby foods and higher serum-transferrin receptors were associated with higher WAZ and lower risk of underweight 5y. Presence of Campylobacter and fecal neopterin >6.8 nmol/L in the first year were associated with increased risk of underweight 5y. Conclusions: Growth indicators 5y were associated with poverty, inappropriate complementary feeding, and infections during the first year of life, which supports the early start of public health interventions for preventing growth delay 5y.